2013
DOI: 10.1039/c3an01204b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced imaging of developed fingerprints using mass spectrometry imaging

Abstract: Latent fingermarks are invisible to the naked eye and normally require the application of a chemical developer followed by an optical imaging step in order to visualize the ridge detail. If the finger deposition is poor, or the fingermark is aged, it can sometimes be difficult to produce an image of sufficient quality for identification. In this work, we show for the first time how mass spectrometry imaging (in this case time-of-flight secondary ion mass spectrometry, ToF-SIMS) can be used to enhance the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 8 publications
0
49
0
Order By: Relevance
“…This may be useful when a fingerprint is smudged or details of the donor are not contained within the fingerprint database. Many techniques have been proposed for these applications, including spectroscopic techniques [30], which lack the selectivity of mass spectrometry methods; chromatography based approaches [22,29] which require considerable sample preparation and consume at least an entire fingerprint; and vacuum based methods [20][21][22][23][24][25], which have lower sample throughput and have been shown to degrade fingerprint chemistry [31].…”
Section: Introductionmentioning
confidence: 99%
“…This may be useful when a fingerprint is smudged or details of the donor are not contained within the fingerprint database. Many techniques have been proposed for these applications, including spectroscopic techniques [30], which lack the selectivity of mass spectrometry methods; chromatography based approaches [22,29] which require considerable sample preparation and consume at least an entire fingerprint; and vacuum based methods [20][21][22][23][24][25], which have lower sample throughput and have been shown to degrade fingerprint chemistry [31].…”
Section: Introductionmentioning
confidence: 99%
“…The technique demonstrated spatial resolution on the order of 100's µm, sufficient for an overall characterization of the analyte distributions, yet insufficient for differentiating much smaller micron size particles or tertiary ridge detail. Alternative high resolution laser desorption [47] and time-of-flight secondary ion mass spectrometry (ToF-SIMS)[48] systems can provide the sub-micrometer spatial resolution necessary for particles sizing and pore imaging.The chemical distribution imaging of another oxidizer, calcium ammonium nitrate, successfully identified the calcium cation (m/z 40 Ca + ), the nitrate anion (…”
mentioning
confidence: 99%
“…However, even for cocaine and heroin the drop in signal intensity was very significant. It was hypothesised that Another group investigated the compatibility workflow between CAF and TOF SIMS 69 . It was shown that TOF SIMS only yielded the detection of very few species 69 .…”
Section: Compatibility With Fingerprint Enhancement Techniques (Fet)mentioning
confidence: 99%
“…It was hypothesised that Another group investigated the compatibility workflow between CAF and TOF SIMS 69 . It was shown that TOF SIMS only yielded the detection of very few species 69 . Low efficiency of detection for this technique was somewhat predicted due to the fact that SIMS is a surface technique and the cyanoacrylate polymerisation generates a layer of polymer which render access to the below surface very challenging.…”
Section: Compatibility With Fingerprint Enhancement Techniques (Fet)mentioning
confidence: 99%
See 1 more Smart Citation